Achromobacter sp. FB-14 mediated morpho-physio-biochemical and molecular improvements in cotton subjected to salt stress - Sidra Batool; Khadija Rafiq; Muhammad Saeed; Atyia Naeem; Muhammad Shahid Munir Chohan; Muhammad Sohail Akram (BMC Plant Biology)
Abstract Background Cotton is considered moderately salt-tolerant, yet the degree of tolerance can vary significantly among different genotypes. Methods and results The current study examined the effects of plant growth-promoting bacterium “Achromobacter sp. FB-14” in two cotton genotypes (FH-326 and FH-941). Under 150 mM salt stress, FH-941 showed a higher accumulation of malondialdehyde (MDA) and hydrogen peroxide (H2O2) i.e. 24.4 and 8.20 µmol g− 1 FW, respectively. Contrarily, FH-326 exhibited higher catalase (CAT) and peroxidase (POD) activities (48.82 & 27.81 Umg− 1 protein, respectively). FB-14 inoculated plants exhibited an increase in chlorophyll a content by 10% (FH-326) and 8% (FH-941). FH-326 exhibited better ion (Na+, K+, Ca+ 2, Mg+ 2) uptake and root-shoot translocation patterns than FH-941. Imposition of salt stress, without FB-14 inoculation, resulted in higher reduction in NHX1, SOS1, and HAK5 gene expression in FH-941 compared to FH-326. While elevated expression of HKT1 was recorded in FH-326 compared to FH-941. A down-regulation of LHCB, GhWRKY3 and GhWRKY34 was recorded in both genotypes except GhWRKY34 was up-regulated in FH-326. Additionally, FB-14 inoculation in FH-941, under salt stress, led to up-regulation of LHCB and GhWRKY3 and GhWRKY34. Conclusions The FH-326 maintained optimum H2O2 and MDA content through POD/CAT activities, balanced ion uptake and gene regulation. The growth of salt-sensitive FH-941 was facilitated by FB-14 inoculation through modulated patterns of ion homeostasis, expression of ion transporter and transcription factors. Further studies involving more cotton genotypes and salt-related molecular markers under bacterial inoculation may assist in devising better strategies to achieve potential yield of cotton.